Effect of pocket feeding of Bombus atratus (Hymenoptera: Apidae) in early colony development stages - PACATEQUE, JOHANNA; CRUZ, PAOLA; AGUILAR, MARLENE LUCÍA; CURE, JOSÉ RICARDO (Revista Colombiana de Entomología, 2012)
With the goal of optimizing the rearing methodology for Bombus atratus in conditions of captivity, the effect of manually providing pollen into the pockets was evaluated under three provisioning combinations: the first four cells (T1), only the first cell (T2) or only the fourth cell (T3). In all three cases the workers also had access to pollen directly on the floor of the rearing box. All the colonies were monitored until emergence of the last worker of the fourth cell. in each combination the number of cells produced, number of workers produced, weight of the workers and their developmental time was evaluated. T1 and T2 were not statistically different for any of the variables evaluated, but they were significantly different from T3 for all of them with the exception of developmental time, which was similar for all combinations. T1 and T2 produced a mean of 22 cells while T3 produced 15 cells. T1 and T2 produced a mean of 26 ± 0.7 and 23.2 ± 2.3 workers, respectively, in the first four cells, while in T3 the mean number was 16.3 ± 2.0 workers. Mean weight of the workers in T1 and T2 was greater (0.19 ± 0.02 and 0.18 ± 0.02 g, respectively) than those in T3 (0.09 ± 0.005 g). the lowest mortality was obtained in T1. it is concluded that pocket feeding in the early stages favors colony growth and development.